2021
DOI: 10.1093/jb/mvab016
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of flippase-like activity by tubulin regulates phosphatidylserine exposure in erythrocytes from hypertensive and diabetic patients

Abstract: Plasma membrane tubulin is an endogenous regulator of P-ATPases and the unusual accumulation of tubulin in the erythrocyte membrane results in a partial inhibition of some their activities, causing hemorheological disorders like reduced cell deformability and osmotic resistance. These disorders are of particular interest in hypertension and diabetes, where the abnormal increase in membrane tubulin may be related to the disease development. Phosphatidylserine is more exposed on the membrane of diabetic erythroc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 52 publications
0
8
0
Order By: Relevance
“…The lipids PS(27:0)-H and PS­(30:2e)-H both belong to phosphatidylserine (PS), which is the most abundant negatively charged glycerophospholipid in eukaryotic membranes. Physiologically, PS mostly exists in the interior of the plasma membrane and in a small amount in the exterior; it would be externalized to the extracellular surface during cell apoptosis induction under pathological factors such as infection, autoimmune attack, mitochondrial function, and so on. It has been reported that PS is more exposed to red blood cells in hypertensive and diabetic patients than in healthy cohorts, which may be attributed to tubulin inhibition of flipping enzyme activity due to the possible inhibition of flippase activity by tubulin . Current studies reported that PS also externalizes to microparticles (MPs) in DKD, causing membrane remodeling.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The lipids PS(27:0)-H and PS­(30:2e)-H both belong to phosphatidylserine (PS), which is the most abundant negatively charged glycerophospholipid in eukaryotic membranes. Physiologically, PS mostly exists in the interior of the plasma membrane and in a small amount in the exterior; it would be externalized to the extracellular surface during cell apoptosis induction under pathological factors such as infection, autoimmune attack, mitochondrial function, and so on. It has been reported that PS is more exposed to red blood cells in hypertensive and diabetic patients than in healthy cohorts, which may be attributed to tubulin inhibition of flipping enzyme activity due to the possible inhibition of flippase activity by tubulin . Current studies reported that PS also externalizes to microparticles (MPs) in DKD, causing membrane remodeling.…”
Section: Discussionmentioning
confidence: 99%
“… 13 15 It has been reported that PS is more exposed to red blood cells in hypertensive and diabetic patients than in healthy cohorts, which may be attributed to tubulin inhibition of flipping enzyme activity due to the possible inhibition of flippase activity by tubulin. 16 Current studies reported that PS also externalizes to microparticles (MPs) in DKD, causing membrane remodeling. The most possible pathological mechanism is MPs formed under high glucose levels, inflammation, lipotoxicity, hypoxia, and uremic toxins.…”
Section: Discussionmentioning
confidence: 99%
“…Diabetes mellitus is associated with prothrombotic alterations . In diabetes, the abundance of PS on the membrane of diabetic erythrocytes and microparticles derived from blood cells is higher than that in healthy cells . In particular, meal intake increased PS-expressing platelet microparticles both in patients with T1D and T2D, with an accompanying increase in procoagulant potential .…”
Section: Ps Function In Diabetes and Altered Prothrombin Levelsmentioning
confidence: 99%
“…54 In diabetes, the abundance of PS on the membrane of diabetic erythrocytes and microparticles derived from blood cells is higher than that in healthy cells. 55 In particular, meal intake increased PS-expressing platelet microparticles both in patients with T1D and T2D, with an accompanying increase in procoagulant potential. 56 However, another clinical experiment conducted with healthy individuals showed that erythrocytederived microparticles exhibit similar PS content and thrombin-related signaling after fasting and after two-meal intake.…”
Section: Prothrombin Levelsmentioning
confidence: 99%
“…As expected, heightened expression of PLSCR1 and increased PS exposure were associated with increased fibrin turnover, which may explain, at least in part, the thrombophilia commonly reported in SLE patients [ 38 ]. An increase in PS scrambling to the outer membrane in erythrocytes has also been associated to other pathologies, such as diabetes and hypertension, which appears to be regulated by tubulin content and distribution and flippase activity [ 39 ]. Further studies should be conducted to elucidate the specific impact of PLSCR1 on this phenomenon.…”
Section: Plscr1 Interactions With Endogenous Proteinsmentioning
confidence: 99%